O panorama da prática de corrida no Brasil: os praticantes de corrida, suas características e os facilitadores e barreiras do desenvolvimento de um programa de prevenção de lesões relacionadas à corrida - Oliveira, Gabriela Martins de (2020)
Context and rationale: Running is one of the most popular and accessible physical activities in the world. However, there is a paucity of evidence on the characteristics and proportion of runners in Brazil. Getting to know the Brazilian population who practice running is extremely important for the development of public health policies aimed at encouraging people to exercise. Also, information on the proportion of runners may serve as a reference for studies related to the running practice. Knowledge on the facilitators and barriers to the development process of a running-related injury prevention programme may help future endeavours in this regard. Objectives: (1) To investigate the proportion of individuals who practice running in Brazil; (2) to investigate the temporal trend in the proportion of runners; (3) to describe the characteristics of Brazilian runners; (4) and to investigate the facilitators and barriers of the process of developing a running-related injury prevention programme. Study design: Repeated cross-sectional study to address objectives 1, 2 and 3; and qualitative study to address objective 4. Population: To investigate objectives 1, 2 and 3, data from participants of Vigitel (Risk Factors Surveillance for Chronic Noncommunicable Diseases) from the Brazilian Ministry of Health were used. To investigate objective 4, individuals participating in the development process of a running-related injury prevention programme were recruited. Results: 2.45% (95% Bayesian credible interval [95% CrI] 1.93 to 3.11) and 5.32% (95% CrI 4.29 to 6.54) of the Brazilian general and active population were runners, respectively. The proportion of Brazilian runners increased by approximately 1.60% (95% CI 1.21 to 2.05) considering the general population, and 2.60% (95% CrI 1.89 to 3.33) considering only the active population over the 12 years of study (2006 to 2017). The most frequent facilitators reported were ‘group meeting’ (32.6%, n=14), ‘contact form’ (20.9%, n=9) and ‘professional motivation’ (16.3%, n=7). The most frequent barriers reported were ‘absence of participants’ (22.9%, n=8), ‘ramblings’ (20.0%, n=7) and ‘little/ lack of moderation’ (14.3%, n=5). Conclusions: There was a 95% probability that the proportion of runners in Brazil is between 2% and 3% in the general population, and between 4% and 7% in the active population. The development of runningrelated injury prevention programmes should be focused on face-to-face meetings with an individualised approach and active moderation.